2017
DOI: 10.1039/c7cc01538k
|View full text |Cite
|
Sign up to set email alerts
|

In situ investigation of degradation at organometal halide perovskite surfaces by X-ray photoelectron spectroscopy at realistic water vapour pressure

Abstract: Near-ambient-pressure X-ray photoelectron spectroscopy enables the study of the reaction of in situ-prepared methylammonium lead iodide (MAPI) perovskite at realistic water vapour pressures for the first time. We show that MAPI decomposes directly to PbI, HI and NH without formation of methylammonium iodide, allowing us to distinguish between alternative mechanisms for the atmospheric degradation reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
81
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(90 citation statements)
references
References 41 publications
8
81
1
Order By: Relevance
“…From the atomic ratio data, it can be concluded that there is no sign of PbI 2 formation. It appears to contradict a previous NAPXPS study, in which the perovskite surface is completely decomposed at 9 mbar of water partial pressure [19]. This contradiction can be justified by the difference in sample fabrication.…”
Section: Resultscontrasting
confidence: 62%
See 1 more Smart Citation
“…From the atomic ratio data, it can be concluded that there is no sign of PbI 2 formation. It appears to contradict a previous NAPXPS study, in which the perovskite surface is completely decomposed at 9 mbar of water partial pressure [19]. This contradiction can be justified by the difference in sample fabrication.…”
Section: Resultscontrasting
confidence: 62%
“…Schlipf et al reported an earlier PbI 2 formation than the appearance of monohydrate in their in-situ XRD measurements [18]. Recent near ambient pressure X-ray photoelectron spectroscopy (NAPXPS) study also claimed the surface of a perovskite thin film prepared by thermal deposition quickly decomposed into PbI 2 at only 30% of relative humidity level [19]. Therefore, a direct degradation pathway leading to PbI 2 may exist, causing premature deterioration of device performance.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the instability/degradation of typical perovskite materials, particularly when placed in a humid environment is extremely problematic; 10 upon exposure to moisture, the most widely used organolead perovskite, methylammonium lead (tri-)iodide (MAPI), degrades into lead iodide with a complete loss of the nitrogen moiety. 11 Many attempts to improve the stability of halide perovskites have been investigated by a variety of approaches, including the use of alternative lead precursors, 12 mixed cations, 13,14 and fabrication of two-dimensional perovskites. 15 Nonetheless, the stability still lags behind industrial photovoltaic standards which typically require a <10% loss in power generation aer utilisation of 20 years.…”
Section: Introductionmentioning
confidence: 99%
“…This result is consistent with the aforementioned conclusion that the PbI 2 complex formed when the tBP was spin‐coated on the perovskite surface. Except from the two main peaks of Pb 4f 7/2 and Pb 4f 5/2 , a small trace of elemental Pb (Pb (0), 136.2 and 141.1 eV) in the tBP‐coated samples was also found, which could be contributing to the decomposition of perovskite unit cells in an ambient atmosphere . Thus, this result magnifies the observed phenomena in that region together with the consideration that the XPS measurement is sensitive to ≈5–10 nm of the top film …”
Section: Resultsmentioning
confidence: 72%